IMPLEMENTASI METODE QIRO’ATI DALAM MENINGKATKAN TAHSIN SISWA TAHFIDZUL QUR’AN DI SEKOLAH MENENGAH PERTAMA QUR’AN ANNAJIHAH KOTA JAMBI - Hilda Dwifa; Agus Salim, TutiIndriyani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the tahsin ability of Qur’anic memorization students and the implementation of the Qiro’ati method in improving their recitation quality at SMP Qur’an AnNajihah, Jambi City. The research used a qualitative approach with data collected through interviews, observations, and documentation. The results show that students who achieved their memorization targets had superior recitation quality, particularly in makhraj, tajwid, mad, and tartil. The Qiro’ati method was implemented in a structured manner during morning sessions before general lessons began, using a jilid system appropriate to each student’s level. This method proved effective in gradually developing accurate recitation. Additionally, the supportive school environment including special scheduling, routine evaluations, and teacher training significantly contributed to improving students' tahsin skills. Students also demonstrated strong enthusiasm and awareness of the importance of tahsin as the foundation of Qur’anic memorization. Thus, the synergy between an appropriate method and a supportive environment is key to the success of the tahsin program at this school.